Wheelchair mobility, motor performance and participation of adult wheelchair users with ARSACS: a cross-sectional study. (19th May 2023) - Bourassa, Julie; Routhier, François; Gagnon, Cynthia; Rahn, Caroline; Hébert, Luc J.; St-Gelais, Raphaël; Rodrigue, Xavier; Brais, Bernard; Best, Krista L.
Abstract: Purpose: Although approximately 45% of adults with Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay (ARSACS) are permanent wheelchair users, this sub population has been less studied. The purpose of this study was to document wheelchair mobility, motor performance, and participation in a cohort of adult wheelchair users with ARSACS. Methods: We recruited 36 manual and powered wheelchair users with ARSACS, aged between 34 and 64 years, for this cross-sectional study. Participants completed measures regarding wheelchair mobility (Wheelchair Skills Test Questionnaire [WST-Q-F], Wheelchair Use Confidence Scale [WheelCon-F] and Wheelchair Outcome Measure [WhOM-F]), motor performance (Scale for the Assessment and Rating of Ataxia [SARA], Disease Severity Index for adults with ARSACS [DSI-ARSACS], Upper Extremity Performance Test for the Elderly [TEMPA], Standardised Finger to Nose Test [SFNT], grip strength, pinch strength, Lower Extremity Motor Coordination Test [LEMOCOT], Berg Balance Scale [BBS], Timed Up and Go [TUG] and 10-meter Walk Test [10mWT]), and participation (Barthel Index, LSA-F and LIFE-H). Results were compared between age groups (≤49 years and ≥50 years), types of wheelchair used, and available reference values. Correlations were computed between wheelchair mobility, upper limb function, and participation. Results: Participants presented limitations regarding wheelchair skills, motor performance, and participation in daily activities. Despite preserved upper limb strength, wheelchair skills, upper and lower limb coordination, standing balance, and functional independence were generally more impaired after 50 years of age and among powered wheelchair users. Significant moderate correlations were found between wheelchair skills and self-efficacy, upper limb strength and coordination, and participation in daily and social activities. Conclusions: This study provided the first data sets describing specific characteristics of manual and powered wheelchair users with ARSACS. It supports a need to offer wheelchair skills training interventions to adults with ARSACS, which could increase their daily and social participation. IMPLICATIONS FOR REHABILITATION: Adult wheelchair users with ARSACS present with limited wheelchair skills, significantly impaired motor performance, and reduced participation that generally decreases with age. This profile may serve as comparative data for clinicians to anticipate disease progression. This study provides the first data on distinguishing characteristics between PWC users and MWC users with ARSACS. The main characteristics of PWC users include more severe functional limitations and motor impairments, as well as limited grip strength that contrasts with the general preservation of this function among other adults with ARSACS. There is a need to offer and evaluate wheelchair skills training interventions in the future for adults with ARSACS. The general preservation of grip and pinch strength observed in this population suggests a potential for improvement. Considering the associations found between wheelchair mobility and participation, such interventions may increase users' daily and social participation.